Review of Aluminum Chip Machining Using Direct Recycling Process - A. R., Yusoff; Mohamad Syahmi, Shahrom (Trans Tech Publications, Switzerland, 2014)

(untitled)
This paper reviews the chain of aluminum Direct Recycling process. Direct Recycling is one of intelligent process to recycle the aluminum waste. The current method for recycle waste aluminum, was affect on the environmental issues. This paper focus on the aluminum waste from machining process, also called chips produced from turning and milling process. From chip collected, next compaction process are compressed to the certain amount pressure for consolidating the materials. Lastly to produce a new material, the process is extrusion process. The most important issue to get a quality of a product is, how to control the pressure during both of process. During this process also available in hot and cold condition. From review, it was that cold compaction process more popular implemented compared to hot compaction. Then almost researchers applied hot extrusion it is because to cover sintering process.